Mother Tongue Based Instruction for Developing Communicative Competence of EFL Learners: Teachers’ Experiences - Pandit, Bhumi Raj (English Language Teaching Perspectives, 2025)
Communicative competence is a prerequisite to acquiring linguistic competences. To develop communicative competence of learners, teachers around the globe have practised various methods and techniques. However, English as a Foreign Language (EFL) learners have difficulties and hesitations when they have to communicate in need. In this context, this research envisaged exploring the experiences of teachers on the use of the mother tongue of learners including the techniques used by them in developing communicative competence. To achieve the objectives, semi-structured interviews with teachers and class observation were carried out. Then, themes were developed to organize the relevant information and to make meanings. Based on the analysis, it is discovered that the mother tongue of the learners helped develop communicative competence in English. It motivated the learners, fostered the practice and improved learners’ communicative competence in a natural setting. Moreover, group/pair works, project-based learning, authentic materials, intercultural syllabus and the use of ICTs) were in practice for developing communicative competence in Nepali community schools. This implies that the use of the mother tongue and blending of the intercultural syllabus with literature including ICT helps develop the communicative competence of learners.